Association of thymoquinone-induced changes in PINK1, DRP1, TFEB, and cytochrome c expression with mitochondrial dynamics and apoptosis in HepG2 and HDF cells - Emrah, Bertan; Senay, Vural Korkut (HUMANA PRESS INC, 2025)
Healthy mitochondria and mitochondrial quality control are essential for vital cell activities. Cell health is fundamentally maintained by the coordinated regulation of processes such as mitochondrial fusion, fission, and mitophagy. Their disruption plays a role in cancer pathogenesis, as well as in many diseases. This study investigated the effects of thymoquinone (TQ), a bioactive compound from Nigella sativa, on mitochondrial dynamics and quality control in Hepatocellular Carcinoma Cells (HepG2) and Human Dermal Fibroblasts (HDF). Results from molecular techniques such as the MTT assay, colony formation assay, wound healing assay, DAPI staining, and JC-1 staining, as well as Real-Time Polymerase Chain Reaction (RT-PCR) and Western blot analysis, were evaluated. TQ treatment caused dose-dependent decreases in cell viability and migration in both cell types, according to the MTT and wound healing assay results. While nuclear morphology assessments with DAPI staining served as a parameter for apoptotic changes, JC-1 analysis revealed a significant loss of mitochondrial membrane potential (Delta Psi m) in HepG2 cells, while a relatively milder decrease was observed in HDF cells. At the molecular level, TQ exposure increased Cytochrome c (Cyt c) and Transcription Factor EB (TFEB) levels in both cell lines, but Dynamin-Related Protein 1 (DRP1) upregulation was more pronounced in HDF cells. Specifically, Western blot results showed an increase in PTEN-Induced Kinase 1 (PINK1) protein in HepG2 cells, but not in HDF cells. These findings suggest that TQ can trigger the mitochondrial stress response in HepG2 cells through DRP1-dependent fission, TFEB-associated lysosomal activation, and PINK1-associated mitophagy signaling. The stronger suppression of Delta Psi m and PINK1 induction in HepG2 suggests an increased likelihood of activation of the intrinsic apoptotic pathway, while the partial preservation of mitochondrial integrity in HDF cells suggests a mild adaptation to stress. Further studies on mitophagy flux, Cyt c intracellular distribution, and TFEB nuclear translocation will be needed to define the mechanisms underlying these cell-type-specific responses.
Keywords: Thymoquinone; HepG2; HDF; PINK1; DRP1; TFEB; Cytochrome c; CANCER CELLS; IN-VITRO; GROWTH; INHIBITION; PARKIN; Oncology